Wildlife Estates Label: European landowner's organization - Kostopoulos, Konstantin, author; van den Brink, Bob, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Small and large estates all over Europe represent major partners in the conservation of biodiversity; they provide space, shelter and living conditions for some of our most iconic species. From the running white-tailed deer of Finland to flights of migrating birds in Spain, estates often provide room for such animals to thrive. The Wildlife Estates project aims to establish a network of exemplary estates. These estates/territories will showcase the simple principles of good management and conservation of wildlife estates all over Europe. After 10 years of experience, more than 150estates in 17 countries and close to 1.000.000 ha labelled, the Wildlife Estates (WE) Label has perfected its method of creating biodiversity, which in turn generates economic, social and ecological stability. Our objective is simple. Use the land to its fullest potential, in a respectful manner, so as to create long term benefits. Apart from a highly beneficial exchange of experience, the initiative has established simple but precise principles for the good territorial management and conservation of 'wildlife' territories throughout Europe, divided up according to the different biogeographical regions of the European Union. The WE label has been developed to recognize and admit good and exemplary management of territories. It creates a system which ensures and demonstrates that the management and the use of natural resources on relevant estates comply with biodiversity and nature conservation principles and aims to be flexible and reproducible. This is why the WE Label is vital; to combine careful management practice with conservation – a private commitment to working for the public good. All those who commit to our principles do so on a voluntary basis, not because their hand is forced by regulation, but because they have a healthy respect for the maintenance of biodiversity. In many cases, this is not only good for nature, but a diverse and healthy estate can provide even more benefits like increased pollination, especially when the aims of the WE Label are combined with those of our Pollinator Network initiative.
The working and introduction of the Wildlife Estate Label in the European Union
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.